In vitro seizure like events and changes in ionic concentration - Antonio, Leandro Leite; Anderson, Marlene Lulie; Angamo, Eskedar Ayele; Gabriel, Siegrun; Klaft, Zin-Juan; Liotta, Agustin; Salar, Seda; Sandow, Nora; Heinemann, Uwe (Journal of Neuroscience Methods, 2016)
Background: In vivo, seizure like events are associated with increases in extracellular K+ concentration, decreases in extracellular Ca2+ concentration, diphasic changes in extracellular sodium, chloride, and proton concentration, as well as changes of extracellular space size. These changes point to mechanisms underlying the induction, spread and termination of seizure like events. Methods: We investigated the potential role of alterations of the ionic environment on the induction of seizure like events-considering a review of the literature and own experimental work in animal and human slices. Results: Increasing extracellular K+ concentration, lowering extracellular Mg2+ concentration, or lowering extracellular Ca2+ concentration can induce seizure like events. In human tissue from epileptic patients, elevation of K+ concentration induces seizure like events in the dentate gyrus and subiculum. A combination of elevated K+ concentration and 4-AP or bicuculline can induce seizure like events in neocortical tissue. Conclusions: These protocols provide insight into the mechanisms involved in seizure initiation, spread and termination. Moreover, pharmacological studies as well as studies on mechanisms underlying pharmacoresistance are feasible.
Created from Fastlane, Scopus look-up
Keywords: Chronic epileptic tissue; Electrolyte changes; Human tissue; Ictogenesis; Increased seizure threshold